2021
DOI: 10.1177/0197918321993100
|View full text |Cite
|
Sign up to set email alerts
|

“New White Ethnics” or “New Latinos”? Hispanic/Latino Pan-ethnicity and Ancestry Reporting among South American Immigrants to the United States

Abstract: This article explores the identification patterns of South American immigrants to the United States, as measured via Hispanic/Latino ethnicity and ancestry reporting on the US Census. Using data from the 2006–2010 and 2011–2015 American Community Survey, my analysis reveals four main findings. First, I show significant heterogeneity in identity patterns and in sociodemographic, immigration, and geographic characteristics between South American and Mexican immigrants in the United States. Second, I find that So… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 26 publications
0
15
0
1
Order By: Relevance
“…This has made whiteness a much more inclusive category in Brazil than in the USA" (Marrow, 2003, p. 428). While many Brazilian immigrants self-classify as racially White in the United States, distancing themselves from the Hispanic/Latino label and experience of otherness, they are perceived as nonwhite and Hispanic/Latino by Americans (Margolis, 1993;Martes, 2007;Schut, 2021). Therefore, the unique racialization process of Brazilian immigrants in the United States is "one of the dilemmas of Brazilian identity construction" (McDonnell & Lourenço, 2009, p. 242).…”
Section: Brazilians Immigrants In the United Statesmentioning
confidence: 99%
See 3 more Smart Citations
“…This has made whiteness a much more inclusive category in Brazil than in the USA" (Marrow, 2003, p. 428). While many Brazilian immigrants self-classify as racially White in the United States, distancing themselves from the Hispanic/Latino label and experience of otherness, they are perceived as nonwhite and Hispanic/Latino by Americans (Margolis, 1993;Martes, 2007;Schut, 2021). Therefore, the unique racialization process of Brazilian immigrants in the United States is "one of the dilemmas of Brazilian identity construction" (McDonnell & Lourenço, 2009, p. 242).…”
Section: Brazilians Immigrants In the United Statesmentioning
confidence: 99%
“…Another Brazilian demographic distinction is their socioeconomic status and education. Generally, Brazilian immigrants have middle to upper socioeconomic status origins in Brazil and more education than the general Brazilian population (Joseph, 2011;Schut, 2021). Brazilian immigrants can somewhat blend into mainstream American neighborhoods.…”
Section: Brazilians Immigrants In the United Statesmentioning
confidence: 99%
See 2 more Smart Citations
“…2 The American Community Survey showed that Argentine, Venezuelan, Brazilian, and Mexican immigrants were most likely to report their race as White (87%, 79%, 75%, and 62%, respectively). 3 This can help elucidate the misconception that most Hispanic/Latino patients have a skin of color. A summary of key elements to consider when studying these populations is depicted in Table I.The authors also found that patients with Medicaid/Health Maintenance Organization insurance had 52% larger defects than those in patients with Medicare.…”
mentioning
confidence: 99%